The Transforming traditional Islamic boarding schools into modern educational institutions: a Systematic Literature Review - Muhammad Saefullah; Raharjo Raharjo; Fihris Fihris; Muammar Sabiq Mulsyah; Satria Kharimul Qolbi (Indonesian Journal of Educational Management and Leadership, 2026)
Purpose – Traditional Islamic boarding schools (pesantren) are required to adapt to educational modernization, technological advancement, and changing societal needs while preserving their Islamic identity. This study aims to analyze the transformation of traditional pesantren into modern educational institutions and to develop a conceptual synthesis of the relationships among Islamic educational transformation, institutional transformation, educational quality, and student well-being. Method – This study employed a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. Literature was retrieved from the Scopus and Google Scholar databases. Eligible studies were critically appraised using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist, resulting in 27 articles that were analyzed through thematic analysis. Findings – The synthesis identified five major themes: Islamic educational transformation, institutional transformation, the modernization of pesantren, educational quality, and student well-being. The findings indicate that the transformation of pesantren is a gradual, multidimensional, and integrated process in which educational transformation serves as the foundation for institutional strengthening, governance modernization, educational quality improvement, and the enhancement of student well-being. Rather than replacing traditional Islamic values, modernization integrates Islamic educational traditions with the demands of contemporary education. The novelty of this study lies in the development of a comprehensive conceptual synthesis that integrates these five dimensions into a unified framework, providing a more holistic perspective on the transformation of pesantren than previous studies.